Formerly Intimate Spaces, Contemporary Makers οf Culture - Antoniou, Klitsa (My University, 2026)
Formerly Intimate Spaces, Contemporary Makers οf Culture: The Country House of Adamantios Diamantis One-day International Symposium | Saturday, November 26, 11 a.m. Ayios Theodoros Pitsilias With Lydia Chatziiakovou, Valentina Sokratous, Dr Gabriel Koureas, Dr Theopisti Stylianou Lambert, Stella Evangelidou, Dr Christina Lambrou Moderator Dr Elena Parpa Organisation Cut Contemporary Fine Arts Lab / Dr Klitsa Antoniou